Direct targeting of oncogenic RAS mutants with a tumor-specific cytosol-penetrating antibody inhibits RAS mutant–driven tumor growth - Shin, Seung Min; Kim, Ji Sun; Park, Seong Wook; Jun, Sei Yong; Kweon, Hye Jin; Choi, Dong Ki; Lee, Dakeun; Cho, Yong Beom; Kim, Yong Sung (Science Advances, 2020)
Oncogenic RAS mutant (RASMUT) proteins have been considered undruggable via conventional antibody regimens owing to the intracellular location restricting conventional-antibody accessibility. Here, we report a pan-RAS–targeting IgG antibody, inRas37, which directly targets the intracellularly activated form of various RASMUT subtypes after tumor cell–specific internalization into the cytosol to block the interactions with effector proteins, thereby suppressing the downstream signaling. Systemic administration of inRas37 exerted a potent antitumor activity in a subset of RASMUT tumor xenografts in mice, but little efficacy in RASMUT tumors with concurrent downstream PI3K mutations, which were overcome by combination with a PI3K inhibitor. The YAP1 protein was up-regulated as an adaptive resistance-inducing response to inRas37 in RASMUT-dependent colorectal tumors; accordingly, a combination of inRas37 with a YAP1 inhibitor manifested synergistic antitumor effects in vitro and in vivo. Our study offers a promising pan-RAS–targeting antibody and the corresponding therapeutic strategy against RASMUT tumors.
Keywords: Anti-tumor activities; Antitumor effect; Colorectal tumors; Systemic administration; Therapeutic strategy; Tumor cells; Tumor growth; Tumor xenografts; Animals; Antineoplastic Agents, Immunological; Cell Proliferation; Disease Models, Animal; Dose-Response Relationship, Drug; Endocytosis; Endosomes; Humans; Immunoglobulin G; Integrin alphaVbeta3; Mice; Mutation; Neoplasms; ras Proteins; Signal Transduction; Xenograft Model Antitumor Assays